Analysis of Several Soil Physical Properties in the Third Generation of Oil Palm Plants at PT. Sinar Pandawa Labuhanbatu - Arya Wiryansyah; Fitra Syawal Harahap; Kamsia Dorliana Sitanggang; Luthfi Fadillah Zamzami (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The physical properties of the soil that need to be considered are the problems of degradation and soil structure due to management functions. In addition, on cultivated land that is not eroded, organic material is lost quickly.This research was carried out through 2 stages of activities, namely field activities and analysis activities. Stages of field activities were carried out at the Kebun Sinar Pandawa Palm Oil Plantation PT. Sinar Pandawa, Labuhanabtu, North Sumatra Province with a height of 28 meters. The method used in this research is a free grid measurement method at a semi-detailed survey level (observation frequency of 1 sample per 500 meters). Carrying out soil sampling at up to 5 sampling points with a distance of 100 meters in the field using a random method, spread over a predetermined area based on the base map. Land Use Research Results withSoil texture at PT. Sinar Pandawa, Labuhanbatu Regency, Sandy Clay, The Bulk Density value shows low, soil porosity is still high, the soil color looks relatively dark, and the soil water content is still relatively normal.